Some Ecotoxicological Considfrations for Use of Pesticides in forestry - Thakur, M. L. (Indian Forester, 1986)
Pesticides constitute an important tool in the pest management. They have contributed significantly in checking the vector borne diseases, insects pests, diseaeses, nematodes, rodents, etc. However, reports on the impact of pesticides and their residues in the biosphere have been appearing quite regularly in recent years. The residues of these chemicals have beon detected almost in every type of organisms such as aquatic and terrestrial fauna, including birds. They are also known to affect the beneficial non-target species and creating disturbances in the equilibrium between the pest species and their enemy complex. Further the sprayed areas are known to get resinfested due to resurgence of the resistant, residual pest population as well as from the surrounding unsprayed areas. Pesticidal control therefore, alone under forestry conditions having crops with long working rotations. is not only hazardous but also uneconomical. It is, therefore, emphasized that an integrated approach, linking all the available control parameters, for various pest species should be evolved and followed for achieving an overall economic, social and environmental values.